Low voltage metal oxide TFT with back-contacted piezoelectric PVDF-HFP coating for pressure sensing applications - Pandey U.; Pal N.; Pal B.N. (My University, 2025)
Li-Alumina (LA) Ion-conducting dielectric thin film has been prepared through the low-cost sol-gel method and is prosperously use to fabricate the metal-oxide based thin-film transistor (MOTFT). This MOTFT shows the high device performance at very low operating voltage (2V). Li-Alumina thin film shows a very high insulating nature due to the high band-gap of the material. Furthermore, because of the Li+ ion conduction a thin film LA, can be has a very high areal capacitance and may be used as a gate dielectric for low operating voltage metal oxide TFTs. Besides, thin film of LA gives low surface roughness due to its amorphous nature resulting decrease in the gate leakage current in TFT. Also, Li-Alumina dielectric has strong compatibility with the SnO2 semiconducting channel in TFT. A SnO2 thin film has been deposited on the top of the Li-Alumina dielectric layer by the solution-processed technique in the top contact bottom gate TFT architecture that works as semiconductor channel of the device. To saturate the drain current in this TFT, only 2.0 V or less drain voltage (VD) is required, with a gate bias of 2.0 V. The obtained value of threshold voltage Vth), carrier mobility (μ) and On/Off ratio of this device are 0.9 V, 1 cm2V-1s-1 and 1.1 x 102. For the application of this TFT as pressure sensor, a piezoelectric material (PVDF-HFP) thin film has been fabricated on the top of the device, that works as a back gate in the device. Channel current of this TFT can be modulated by applying pressure on the PVDF-HFP thin film. Hence, this device works as piezoelectric back-contacted TFT that can also be considered TFT as a pressure sensor. Additionally, this metal oxide based pressure sensor shows excellent performance in terms of the sensitivity, linearity and response time of the device. © 2022 IEEE.